Peramalan Jumlah Penumpang LRT Sumsel dengan Metode Exponential Smoothing - Lailiyah, Riski Rahmatul; Agustiani, Riza (UNIB Press, 2022)
Forecasting is critical in the pandemic sector as part of the effort to adapt the post-pandemic system, particularly in transportation. This research carried out on the South Sumatra Integrated Railroad (LRT) in the post-pandemic Covid-19 period. Forecasting is done in this study using the exponential smoothing method using alpha that is α=0.1, α=0.5, and α= 0.9. Comparison with the smallest error using the exponential smoothing method dropped the choice at alpha 0.1 with the smallest error calculation value. Forecasting using the exponential smoothing method with 0.1 alpha sample data on the number of LRT Sumsel passengers during the Covid-19 period in 2020 produces a forecast of 66,538 passengers with an error rate of Mean Absolute Deviation (MAD)=9,486, Mean Square Error (MSE)=1,150, and Mean Absolute Percentage Error (MAPE)=24.58%. Meanwhile, from the sampel data on the number of South Sumatra LRT passengers on post-pandemic Covid-19 period in 2022, it produced a forecast of 187,566 passengers with Mean Absolute Deviation (MAD) = 25,816, Mean Square Error (MSE) = 9,477, and Mean Absolute Percentage Error (MAPE) = 16.60%.